MAKNA EKOLOGI BUDAYA LEKSIKON PER-UNDAGI-AN BAHASA BALI - Mahardika, I Putu Permana (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 26 No 1 (2019): MaretDO - 10.24843/ling.2019.v26.i01.p05, 2019)
This research aims at describing the ecological meaning based on undagies lexicon in Balinese. The data collected by direct observation and combined with note-taking. The collected data was analyzed by applying the theory of ecolinguistics and semiotic. The lexicon used in this research were; (a) wood lexicon; (b) stone lexicon; and (c) kekarangan lexicon. Based on the analysis conducted, it was found that the undagies lexicon has an ecological meaning based on Hindus literaries such as; Aji Jan?ntaka , Asta Kosali , Asta Bhumi , and Kekawin Bhom?ntaka .